Medicine and Treatment through the Book of Prophet Judgment in the Medical Industries by Alaa AI-Din AI-Kahhal (d.720 Ah_1320Ad) - Gassem, Suhad Nasslf (Journal of Tikrit University for Humanities, 2023)
Medicine is one of human professions that is concerned with the health and quality of the individual. The Islamic Law is an integrated law in all aspects of life. it also emphasizes the importance of legislation sources in relation to human health. This study aims to explain the prophetic rules in diseases and their treatment according to prophetic Sunnah confirmed by the hadith. The research is divided into two parts that deal with the topic of prophetic medicine, the most important commandments, and prophetic measures to preserve health.